Pelatihan Teknologi Tepat Guna (TTG) Pengolahan Limbah Ternak di Desa Tambah Dadi Kecamatan Purbolinggo - Diah Reni Asih; Miftahuddin Ahmad; Rohmatul Anwar; Dwi Subakti Prastiyo (Lembaga Pengembangan Kinerja Dosen, 2026)
Appropriate Technology Training (TTG) in Tambah Dadi Village, Purbolinggo Subdistrict aims to improve the community's understanding and ability to manage livestock waste more efficiently. Often, livestock waste produced in this village is not utilized properly. Training participants will be introduced to various waste management methods that can be used as sources of organic fertilizer and organic compost. The training includes awareness-raising, demonstrations, and hands-on practice in processing waste into useful products such as organic fertilizer. The results of the training show that participants are able to make organic fertilizer from livestock waste. It is hoped that this activity will serve as an example for other villages to manage livestock waste in a more sustainable manner, which will improve agricultural and livestock yields in the area and increase the welfare of farmers in Tambah Dadi Village. The results of this activity show that the application of appropriate technology not only focuses on waste management, but also aims to improve the economic conditions of the community.